2016
DOI: 10.1021/acs.nanolett.6b01180
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Oriented Arrays of ReS2 Nanosheets for Electrochemical Energy Storage and Electrocatalysis

Abstract: Transition-metal dichalcogenide (TMD) nanolayers show potential as high-performance catalysts in energy conversion and storage devices. Synthetic TMDs produced by chemical-vapor deposition (CVD) methods tend to grow parallel to the growth substrate. Here, we show that with the right precursors and appropriate tuning of the CVD growth conditions, ReS2 nanosheets can be made to orient perpendicular to the growth substrate. This accomplishes two important objectives; first, it drastically increases the wetted or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
207
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(218 citation statements)
references
References 46 publications
11
207
0
Order By: Relevance
“…The distance between the two peaks in the line intensity profile shown in the bottom of Figure 2e is ≈0.307 nm, which matches well with the value of the unit cell parameter of MoS 2 39. 2D materials with high‐quality vertically oriented few‐layer structures have been reported to be ideal materials for photodetectors, energy storage, catalysis, and edge emitter devices because of their high active surface areas, strong light absorptions, and quick longitudinal intralayer transport speeds 34, 35, 36, 37, 40, 41, 42. Therefore, these V‐MoS 2 nanosheets may also have great potential applications in multifarious fields.…”
Section: Experimental and Characterizationsupporting
confidence: 72%
See 1 more Smart Citation
“…The distance between the two peaks in the line intensity profile shown in the bottom of Figure 2e is ≈0.307 nm, which matches well with the value of the unit cell parameter of MoS 2 39. 2D materials with high‐quality vertically oriented few‐layer structures have been reported to be ideal materials for photodetectors, energy storage, catalysis, and edge emitter devices because of their high active surface areas, strong light absorptions, and quick longitudinal intralayer transport speeds 34, 35, 36, 37, 40, 41, 42. Therefore, these V‐MoS 2 nanosheets may also have great potential applications in multifarious fields.…”
Section: Experimental and Characterizationsupporting
confidence: 72%
“…However, vertically oriented multilayer MoS 2 , which has the advantages of both strong light absorption and quick longitudinal in‐plane transport, may show huge potential in optoelectronic devices; e.g., in 2015, Wang et al first deposited the vertically standing layered MoS 2 directly on Si substrate to form MoS 2 /Si heterojunction photodetector by magnetron sputtering and realized an extremely high detectivity (≈10 13 Jones) and an ultrafast response time (≈3 µs) 33. Considering the outstanding properties and great potential in optoelectronic devices, recently, researchers have begun trying to synthesize other 2D materials of this vertically layered structure, and several large‐area, high‐quality, and vertically oriented few‐layered 2D nanosheets have been successfully prepared by chemical vapor deposition (CVD) 34, 35, 36, 37. Notably, compared with other preparation methods, the quality of CVD‐prepared MoS 2 should be much better due to the relatively intact layered structure and fewer defects.…”
Section: Introductionmentioning
confidence: 99%
“…[106] It has shown that ReS2 can be exploited as polysulfide immobilizer, and therefore, used to suppress the dissolution of polysulfides and enhance the cycle stability of the Li-S batteries. [107] The effect of ReS2 in (Figure 12 c). Moreover, binding polysulfides showed higher binding energy (2.24 to 2.66 eV) on ReS2 surfaces than that of carbon (~0.5 to 1 eV).…”
Section: Energy Storagementioning
confidence: 99%
“…[121] Like other TMDs, ReS2 has shown 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 good HER performance -better than the more commonly used TMDs. [107,122] Gao et al [107] has tested HER on CVD grown ReS2@Au, and found that it exhibited ~ 200 mV less overpotential (η) than bare Au. Further decrease in overpotential (η < 100 mV) was achieved after lithiation using n-butyl lithium treatment (Figure 15 a).…”
Section: Photocatalytic and Electrocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…This opens the exciting prospect to achieve optoelectronic functionality from bulk ReX 2 of a form that can only be realized by complex fabrication of single-layer samples and devices in group VI semiconducting TMDCs. Coupled with a pronounced anisotropy in their measured optical and electrical properties [7][8][9][10], ReX 2 materials are therefore important compounds for expanding the functionality of the TMDC class, and they have potential for next-generation technologies [11,12]. The electronic structure underpinning their striking optoelectronic properties, however, remains almost completely unexplored experimentally to date.…”
Section: Introductionmentioning
confidence: 99%